Ta’lim Al-Lughah Al-Arabiyah li An-Nathiqin bi Ghairiha Raqmiyan - Naji, Mohammed; Malmus, Anas (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
This paper seeks to shed light on the extent to which technological applications contribute to improving and improving the process of teaching Arabic to non-native speakers, in addition to measuring the extent to which the field of teaching Arabic to non-native speakers is open to technological developments, by presenting and presenting some digital applications that can be invested in Arabic language classes. For non-native speakers, which aims to improve and renew the process of teaching Arabic to non-native speakers with distinction. Based on the foregoing, this paper stems from two main questions: 1) Has the field of teaching Arabic to non-native speakers opened up to technological development in a way that leads to its facilitation and modernization? 2) What role do digital applications and websites play in facilitating and improving the process of teaching Arabic to non-native speakers? ØªØ³Ø¹Ù‰ Ù‡Ø°Ù‡ Ø§Ù„ÙˆØ±Ù‚Ø© Ø¥Ù„Ù‰ ØªØ³Ù„ÙŠØ· Ø§Ù„Ø¶ÙˆØ¡ Ø¹Ù„Ù‰ Ù…Ø¯Ù‰ Ø¥Ø³Ù‡Ø§Ù… Ø§Ù„ØªØ·Ø¨ÙŠÙ‚Ø§Øª Ø§Ù„ØªÙƒÙ†ÙˆÙ„ÙˆØ¬ÙŠØ© ÙÙŠ ØªØ¬ÙˆÙŠØ¯ ÙˆØªØØ³ÙŠÙ† Ø¹Ù…Ù„ÙŠØ© ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨ØºÙŠØ±Ù‡Ø§ØŒ Ø¹Ù„Ø§ÙˆØ© Ø¹Ù„Ù‰ Ù‚ÙŠØ§Ø³ Ù…Ø¯Ù‰ Ø§Ù†ÙØªØ§Ø Ù…Ø¬Ø§Ù„ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨ØºÙŠØ±Ù‡Ø§ Ø¹Ù„Ù‰ Ø§Ù„ØªØ·ÙˆØ±Ø§Øª Ø§Ù„ØªÙƒÙ†ÙˆÙ„ÙˆØ¬ÙŠØ©ØŒ ÙˆØ°Ù„Ùƒ Ù…Ù† Ø®Ù„Ø§Ù„ Ø¹Ø±Ø¶ ÙˆØªÙ‚Ø¯ÙŠÙ… Ø¨Ø¹Ø¶ Ø§Ù„ØªØ·Ø¨ÙŠÙ‚Ø§Øª Ø§Ù„Ø±Ù‚Ù…ÙŠØ© Ø§Ù„Ù…Ù…ÙƒÙ† Ø§Ø³ØªØ«Ù…Ø§Ø±Ù‡Ø§ ÙÙŠ ÙØµÙˆÙ„ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨ØºÙŠØ±Ù‡Ø§ØŒ ÙˆØ§Ù„ØªÙŠ ØªÙ‡Ø¯Ù Ø¥Ù„Ù‰ ØªØ¬ÙˆÙŠØ¯ ÙˆØªØ¬Ø¯ÙŠØ¯ Ø¹Ù…Ù„ÙŠØ© ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨ØºÙŠØ±Ù‡Ø§ Ø¨Ø§Ù…ØªÙŠØ§Ø². Ø¨Ù†Ø§Ø¡ Ø¹Ù„Ù‰ Ù…Ø§ ØªÙ‚Ø¯Ù…ØŒ ÙØ¥Ù† Ù‡Ø°Ù‡ Ø§Ù„ÙˆØ±Ù‚Ø© ØªÙ†Ø·Ù„Ù‚ Ù…Ù† Ø³Ø¤Ø§Ù„ÙŠÙ† Ø£Ø³Ø§Ø³ÙŠÙŠÙ† Ù‡Ù…Ø§: 1) Ù‡Ù„ Ø§Ù†ÙØªØ Ù…Ø¬Ø§Ù„ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨ØºÙŠØ±Ù‡Ø§ Ø¹Ù„Ù‰ Ø§Ù„ØªØ·ÙˆØ± Ø§Ù„ØªÙƒÙ†ÙˆÙ„ÙˆØ¬ÙŠ Ø¨Ø§Ù„Ø´ÙƒÙ„ Ø§Ù„Ø°ÙŠ ÙŠØ¤Ø¯ÙŠ Ø¥Ù„Ù‰ ØªÙŠØ³ÙŠØ±Ù‡ ÙˆØªØØ¯ÙŠØ«Ù‡ØŸ 2) ÙˆÙ…Ø§ Ø§Ù„Ø¯ÙˆØ± Ø§Ù„Ø°ÙŠ ØªØ¶Ø·Ù„Ø¹ Ø¨Ù‡ Ø§Ù„ØªØ·Ø¨ÙŠÙ‚Ø§Øª ÙˆØ§Ù„Ù…ÙˆØ§Ù‚Ø¹ Ø§Ù„Ø±Ù‚Ù…ÙŠØ© ÙÙŠ ØªÙŠØ³ÙŠØ± ÙˆØªØ¬ÙˆÙŠØ¯ Ø¹Ù…Ù„ÙŠØ© ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨ØºÙŠØ±Ù‡Ø§ØŸ